Occupational and Non-Occupational Lead Exposure in Iraq: Clinical Findings and Protective Measures - Luay Mohammed; Manoochehr Karami; Yadollah Mehrabi; Seyed Hashemi Nazari (The Indonesian Journal of Occupational Safety and Health, 2026)
Introduction: Lead exposure is an important occupational and environmental health problem, especially in the industrial environment. This study determined blood lead levels, associated clinical manifestations and protective measures among petrol refinery workers and population in nearby areas in Kirkuk City, Iraq. Methods: A cross-sectional study was done with 357 workers in petrol refinery and people who live in the nearby city and suburbs. Data were obtained using structured interviews, physical examination and laboratory measurement of blood lead levels. Information regarding occupational history and clinical symptoms and the protection measures was collected. Binary and multivariable logistic regression analyses were performed to determine factors associated with elevated blood lead levels (eBLLs). Results: Longer time of employment and increased time outdoors were significantly associated elevated of BLLs (p<0.05). The workers who use of masks and gloves, machine guards, and consumption of milk in the workplaces were found having lower BLLs (all p<0.05). Workers who had high lead concentrations were positively associated with reporting a metallic taste in the mouth (OR=2.52, p=0.024). Conclusion: Lead occupational and non-occupational exposures in Kirkuk are associated with the negative clinical outcomes. Implementation of the relevant measures of protection strategies have been correlated to reduced BLLs, therefore, pointing at the significance of the enhanced occupational safety practices and preventive actions to decrease the adverse health outcomes on the workers and the community overall.